Aeration performance of weirs: Part 1 - Baylar, Ahmet; B?gatur, Tamer (My University, 2001)
The aeration potential of weirs in rivers is well known. An experimental investigation into the performance of sharp-crested weirs recirculating systems is described. The effects of varying the shape of the weir were examined. The influences of water temperature, water quality, tailwater depth, drop height and weir discharge on oxygen transfer efficiency were investigated. The results will be reported in part 2 of the article.
Keywords: Aeration; River; Weir